(untitled) (Trabalho & Educação, 2018)
This dissertation constituted a simple quantitative-qualitative case study and aimed to understand how the actions of Permanent Education in Health are developed for the interdisciplinary health team work of a public maternity in Minas Gerais. As theoretical references for the research are: the National Policy of Permanent Education in Health (2004), the educational dimension of work and the reflection on professional practices. The policy cited is based on the assumption that lifelong education and health is education at work, work and work in the different health services to promote the development of the health worker and, consequently, the improvement of the health of populations. The educational dimension of the work refers to the transformative potential that the work provides to the workers when being transformed by and for the work - these conceptions are sustained in the explicit one by Karl Marx on the work. The reflection on professional practices are anchored in the assumptions of... ___ Esta dissertação constituiu em um estudo de caso simples de caráter quanti-qualitativo e teve como objetivo compreender como são desenvolvidas as ações de Educação Permanente em Saúde para a formação no trabalho da equipe interdisciplinar de saúde de uma maternidade pública mineira. Como referenciais teóricos para a pesquisa têm-se: a Política Nacional de Educação Permanente em Saúde (2004), a dimensão educativa do trabalho e a reflexão sobre as práticas profissionais. A política citada parte do pressuposto de que a educação permanente em saúde é a educação no trabalho, pelo trabalho e para o trabalho nos diferentes serviços de saúde para promover o desenvolvimento do trabalhador da saúde e, consequentemente, a melhoria da saúde das populações. A dimensão educativa do trabalho refere-se ao potencial transformador que o trabalho proporciona aos trabalhadores ao serem transformados pelo e para o trabalho- tais concepções se sustentam no explicitado por Karl Marx acerca do trabalho. A reflexão sobre as práticas profissionais estão ancoradas nos pressupostos da formação do profissional reflexivo e da reflexão-na-ação de...